Investigating the relevance of maximal speed and acceleration in varsity-level female ice hockey players - Gamble, A. S. D.; Thompson, K. M. A.; Bigg, J. L.; Pignanelli, C.; Spriet, L. L.; Burr, J. F. (International Journal of Sports Physiology and Performance, 2024)
Purpose To characterize and compare female ice hockey players` peak skating speed and acceleration ability during linear sprints and gameplay. We also sought to quantify the time spent at various speeds and the frequency of accelerations at different thresholds during games.